Descrição do encéfalo e do ouvido interno de Pterodactylus (Pterosauria) - Cardozo, Filipe Gratz (2019)
The genus Pterodactylus (Pterosauria, Archaeopterodactyloidea) has a great historical importance for housing the first pterosaur specimen described by science. However, even showing such an importance, to this day its endocast was never studied before using X-ray CT-scan. With the objective of describing its brain, in this study we tomographed the braincases of the holotypes of P. antiquus (SNSB/BSPG AS I 739) and P. kochi (SNSB/BSPG AS XIX 3) and reconstructed the endocasts digitally. We discovered that these organs were more similar to the ones of pterosaurs from the clade Archaeopterodactyloidea, to which the genus belongs, than of other archosaurs and showed adaptations to the flight such as well developed flocculus e optic lobes. Moreover, for the first time we had a glimpse of the semicircular canals, unknown until then. By positioning the lateral semicircular canal horizontally, we discovered that the holotype of P. antiquus kept an alert posture of 17°. Finally, we compared informations about Pterodactylus to ones about other flying archosaurs of the Solnhofen Archipelago available in literature and discovered that Pterodactylus probably didn’t compete with them for the same resources